2018
DOI: 10.1136/esmoopen-2017-000317
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes from the use of regular imaging to detect relapse in high-risk cutaneous melanoma

Abstract: BackgroundAgreement on the utility of imaging follow-up in patients with high-risk melanoma is lacking. A UK consensus statement recommends a surveillance schedule of CT or positron-emission tomography-CT and MRI brain (every 6 months for 3 years, then annually in years 4 and 5) as well as clinical examination for high-risk resected Stages II and III cutaneous melanoma. Our aim was to assess patterns of relapse and whether imaging surveillance could be of clinical benefit.Patients and methodsA retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Regarding timing, over half of relapses occur within 1 year of diagnosis, and the significant majority occur within 3 years (Table ) . Risk of recurrence for all melanoma patients approaches zero, but relapses after 10 years are well documented.…”
Section: Patterns Of Recurrencementioning
confidence: 99%
See 4 more Smart Citations
“…Regarding timing, over half of relapses occur within 1 year of diagnosis, and the significant majority occur within 3 years (Table ) . Risk of recurrence for all melanoma patients approaches zero, but relapses after 10 years are well documented.…”
Section: Patterns Of Recurrencementioning
confidence: 99%
“…A main focus of discussion is whether surveillance CT will actually detect recurrences in a meaningful proportion of asymptomatic patients before those patients might prompt work‐up and detection by their provider. The detection of recurrences by surveillance CT scans has been reported to be between 24% and 59% when reviewing late stage II and stage III disease . Several more recent studies found that CT scans first detect at least half of systemic recurrences .…”
Section: Surveillance Modalitiesmentioning
confidence: 99%
See 3 more Smart Citations